Efficacy of Ifosfamide-Cisplatin-Etoposide (ICE) Chemotherapy for a CNS Germinoma in a Child With Down Syndrome. Issue 1 (January 2017) - Nodomi, Seishiro; Umeda, Katsutsugu; Ueno, Hiroo; Saida, Satoshi; Hiramatsu, Hidefumi; Funaki, Takeshi; Arakawa, Yoshiki; Mizowaki, Takashi; Adachi, Souichi; Heike, Toshio
Abstract : Intracranial germ cell tumor is sometimes associated with Down syndrome; however, no optimal treatment has been developed due to the high risk of recurrence and treatment-related mortality. Here, we report on a patient with an intracranial germinoma in the bilateral basal ganglia. The patient received 3 courses of ifosfamide-cisplatin-etoposide in combination with whole-brain irradiation (24 Gy), with no serious complications. The patient is alive and disease free 16 months after the initial diagnosis. This regimen is a feasible treatment for intracranial germ cell tumor associated with Down syndrome, although careful attention must be paid to the increased risk for severe infection.